Systematic Analysis of the Use of Socio Scientific Issues-Oriented Mobile Learning as a Science Learning Media to Improve the Critical Thinking Skills of Elementary School Students - Euis Lidya Wati; Ika Lestari; Firmanul Catur Wibowo (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study systematically analyzes the implementation of socio-scientific issues–oriented mobile learning to foster elementary students’ critical thinking in science. A Systematic Literature Review following the PRISMA protocol with qualitative synthesis examined ten peer-reviewed articles (2021–2025) meeting strict inclusion criteria. Selected studies integrated mobile learning with socio-scientific issues in elementary science and explicitly measured critical thinking. Findings show consistent moderate-to-high improvement, with N-Gain scores ranging from 0.59 to 0.80. Implementations were mainly associated with problem-based learning combined with guided inquiry. Effective designs integrated interactive multimedia, augmented reality, and Android-based platforms to enable flexible, ubiquitous learning. Frequently addressed issues included environmental pollution, food waste management, and local ecosystem conservation, providing authentic contexts for multi-perspective analysis. Overall, the review confirms that socio-scientific issues–oriented mobile learning is a promising pedagogical approach for promoting higher-order thinking in elementary science, while highlighting the need for adequate technological infrastructure and strong teacher digital competence to ensure effective implementation.